Gut microbiota development in mice is affected by hydrogen peroxide produced from amino acid metabolism during lactation. Issue 3 (15th November 2018) - Shigeno, Yuko; Zhang, Haolin; Banno, Taihei; Usuda, Kento; Nochi, Tomonori; Inoue, Ryo; Watanabe, Gen; Jin, Wanzhu; Benno, Yoshimi; Nagaoka, Kentaro
ABSTRACT: The development of gut microbiota during infancy is an important event that affects the health status of the host; however, the mechanism governing it is not fully understood, l ‐Amino acid oxidase 1 (LAO1) is a flavoprotein that catalyzes the oxidative deamination of particular l ‐amino acids and converts them into keto acids, ammonia, and H2 O2 . Our previous study showed that LAO1 is present in mouse milk and exerts protection against bacteria by its production of H2 O2 . The data led us to consider whether LAO1, H2 O2, or both could impact infant gut microbiota development via mother's milk consumption in mice. Different gut microbiota profiles were observed in the wild‐type (WT) and LAO1 ‐knockout mouse pups. The WT pups' microbiota was relatively simple and composed of only a few dominant bacteria, such as Lactobacillus, whereas the lactating knockout pups had high microbiota diversity. Cross‐fostering experiments indicated that WT milk (containing LAO1) has the ability to suppress the diversity of microbiota in pups. We observed that the stomach content of pups fed WT milk had LAO1 proteins and the ability to produce H2 O2 . Moreover, culture experiments showed that Lactobacillus was abundant in the feces of pups fed WT milk and that Lactobacillus was more resistant to H2 O2 than Bifidobacterium and Escherichia . Human breast milk produces very little H2 O2, which could be the reason for Lactobacillus not being dominant in the feces of breast‐fed human infants. In mouse mother's milk, H2 O2 is generated from the process of free amino acid metabolism, and H2 O2 may be a key player in regulating the initial acquisition and development of gut microbiota, especially growth of Lactobacillus, during infancy.—Shigeno, Y., Zhang, H., Banno, T., Usuda, K., Nochi, T., Inoue, R., Watanabe, G., Jin, W., Benno, Y., Nagaoka, K. Gut microbiota development in mice is affected by hydrogen peroxide produced from amino acid metabolism during lactation. FASEB J. 33, 3343–3352 (2019). www.fasebj.org